Blockade of TGF-β signaling with novel synthetic antibodies limits immune exclusion and improves chemotherapy response in metastatic ovarian cancer models. (1st February 2019) - Newsted, Daniel; Banerjee, Sunandan; Watt, Kathleen; Nersesian, Sarah; Truesdell, Peter; Blazer, Levi L.; Cardarelli, Lia; Adams, Jarrett J.; Sidhu, Sachdev S.; Craig, Andrew W.
ABSTRACT: Epithelial ovarian cancer (EOC) is a leading cause of cancer-related death in women. EOC is often diagnosed at late stages, with peritoneal metastases and ascites production. Current surgery and platinum-based chemotherapy regimes fail to prevent recurrence in most patients. High levels of Transforming growth factor-β (TGF-β) within ascites has been linked to poor prognosis. TGF-β signaling promotes epithelial-mesenchymal transition (EMT) in EOC tumor cells, and immune suppression within the tumor microenvironment, with both contributing to chemotherapy resistance and metastasis. The goal of this study was to develop specific synthetic inhibitory antibodies to the Type II TGF-β receptor (TGFBR2), and test these antibodies in EOC cell and tumor models. Following screening of a phage-displayed synthetic antigen-binding fragment (Fab) library with the extracellular domain of TGFBR2, we identified a lead inhibitory Fab that suppressed TGF-β signaling in mouse and human EOC cell lines. Affinity maturation of the lead inhibitory Fab resulted in several derivative Fabs with increased affinity for TGFBR2 and efficacy as suppressors of TGF-β signaling, EMT and EOC cell invasion. In EOC xenograft and syngeneic tumor models, blockade of TGFBR2 with our lead antibodies led to improved chemotherapy response. This correlated with reversal of EMT and immune exclusion in these tumor models with TGFBR2 blockade. Together, these results describe new inhibitors of the TGF-β pathway that improve antitumor immunity, and response to chemotherapy in preclinical EOC models.